REGRESSION MODELING OF THE STRENGTH PROPERTIES OF CONCRETE REINFORCED WITH POLYPROPYLENE FIBER AND ALKALI RESISTANT GLASS FIBRE (Nigerian Journal of Technology, 2018)
This paper presents the result of the regression modeling of the strength properties of hybrid fiber reinforced concrete made with polypropylene fiber (PPF) and alkali resistant glass fibre (ARGF). The fibres were added to grade 25 concrete at different proportion of 0.5%, 1.0%, 1.5% and 2.0% of volume of concrete. A total of sixty three cubes samples were tested for compressive strength, twenty four cylindrical samples for split tensile strength and twenty four beam samples for flexural strength. Maximum compressive strength was attained at 1.5% fibre volume with hybrid fibre ratio of 80% ARGF and 20% PPF, maximum split tensile strength was attained at 1.0% fibre volume with hybrid fibre ratio of 80% ARGF and 20% PPF. The beam samples attained its maximum flexural strength at 1.0% fibre volume with hybrid fibre ratio of 60% ARGF and 40% PPF. Empirical expressions were established by using multiple regression analysis to predict the compressive, split tensile and flexural strengths of the hybrid fibre reinforced concrete made with PPF and ARGF. The predicted values compared favourably with the experimental results from all specimens.  http://dx.doi.org/10.4314/njt.v37i4.6